A Baby Feeding Nipple: Simple, Cost effective, and Safe Technique for Removal of Denture - Gupta, Gaurav Kumar; Gawande, Atul; Sharma, Deepak; Nijhawan, Sandeep (Journal of Digestive Endoscopy, 2019)
Introduction: Denture ingestion occurs commonly in the elderly and frequently impacted in the esophagus due to the sharp edges. This can lead to serious complications such as perforation. We are describing here a simple, cost effective and safe technique for removal of dentures.Material and methods: We used a handmade hood protector made from baby feeding nipple with rat-toothed forceps to safely remove ingested denture in two middle aged patients. Both patients had subcutaneous emphysema.Results: Dentures were removed successfully in both patients. Following denture removal, endoscopic examination of the esophagus did not show any sign of mucosal damage, ulceration, bleeding, or perforation.Conclusion: We successfully and safely removed denture from the stomach using handmade hood designed from a baby feeding tube. It may be beneficial for wide visual field and safety. It is an easy, effective, and safe design for the removal of sharp foreign bodies like dentures.
Keywords: baby feeding nipple; denture; endoscope